Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1002/ange.201603920
|View full text |Cite
|
Sign up to set email alerts
|

Metal Vacancy Ordering in an Antiperovskite Resulting in Two Modifications of Fe2SeO

Abstract: Supportinginformation and the ORCID identification numbers for the authors of this article can be found under http://dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…15 Recently, a novel antiperovskite (Fe 2 □)SeO with two different orderings of metal vacancies (□) was discovered. 16 By chemically substituting 1 Fe 2+ for 2 Li + , the cubic antiperovskites (Li 2 Fe)ChO (Ch = S, Se) were synthesized, and their preliminary performances as cathodes in batteries account for promising properties. 17 However, only macroscopic investigations and ex situ data have been reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…15 Recently, a novel antiperovskite (Fe 2 □)SeO with two different orderings of metal vacancies (□) was discovered. 16 By chemically substituting 1 Fe 2+ for 2 Li + , the cubic antiperovskites (Li 2 Fe)ChO (Ch = S, Se) were synthesized, and their preliminary performances as cathodes in batteries account for promising properties. 17 However, only macroscopic investigations and ex situ data have been reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…16 However, the key challenges are how to dope large amount of transition metals into the lattice and whether the structure remains stable during Li extraction and insertion. Inspired by a new type of cation vacancy ordered antiperovskite Fe 2 SeO, 52 in which one-third of the cation sites are vacant, Lai et al 29 53 found that Fe could also be substituted by other transition-metal elements such as Mn or Co. It indicated that the crystal structure of the antiperovskite cathode has extraordinary chemical flexibility, which offers many possibilities for the performance improvement.…”
Section: Transition Metal-based Antiperovskites As Electrodesmentioning
confidence: 99%
“…By chemical substitutions in the cation-vacancy-ordered anti-perovskite (Fe 2 □)SeO (□ = vacancy), 12 new lithium battery cathode materials (Li 2 Fe)ChO (Ch = S, Se) with cubic anti-perovskite structures were discovered. 13 These materials are cheap, can be easily produced, and withstand high charging rates, making them competitive for commercial use.…”
Section: Introductionmentioning
confidence: 99%